Pharmacogenomics as a Tool to Limit Acute and Long-Term Adverse Effects of Chemotherapeutics: An Update in Pediatric Oncology - Emma C. Bernsen; Melanie M. Hagleitner; Theodorus W. Kouwenberg; Lidwien M. Hanff (Frontiers in Pharmacology, 2020)
In the past decades, new cancer treatments have been introduced in pediatric oncology leading to improvement in clinical outcomes and survival rates. However, due to inter-individual differences, some children experience severe chemotherapy-induced toxicities or a poor clinical outcome. An explanation for the diversity in response to chemotherapy is genetic variation, leading to differences in expression and activity of metabolizing and transport enzymes as well as drug targets. Pharmacogenetic testing has emerged as a promising tool to predict and limit acute and long-term adverse effects in patients. However, in pediatric oncology, limited number of patients and a considerable diversity in study results complicate the interpretation of test results and its clinical relevance. With this review, we provide an overview of new developments over the past four years regarding relevant polymorphisms related to toxicity in pediatric oncology. The following chemotherapeutics and associated toxicities are discussed: alkylating agents, anthracyclines, asparaginase, methotrexate, platinum compounds, steroids, thiopurines, topoisomerase inhibitors, and vinca alkaloids. Our review identifies several questions regarding the role of genetic variants in chemotherapy-induced toxicities. Ambiguities in the literature stem from small population sizes, differences in (statistical) interpretation and variations in sequencing technologies as well as different clinical outcome definitions. Standardization of clinical outcome data and toxicity definitions within electronic health records combined with the increased availability of genomic sequence techniques in clinical practice will help to validate these models in upcoming years.